Atomistic studies of defects in bcc iron: dislocations and gas bubbles - Hayward, Erin G. (Georgia Institute of Technology, 2012)
The structure and interactions of the defects in material on an atomistic scale ulti- mately determine the macroscopic behavior of that material. A fundamental understanding of how defects behave is essential for predicting materials failure; this is especially true in an irradiated environment, where defects are created at higher than average rates. In this work, we present two different atomistic scale computational studies of defects in body centered cubic (bcc) iron. First, the interaction energies between screw dislocations (line defects) and various kinds of point defects will be calculated, using anisotropic linear elastic theory and atomistic simulation, and compared. Second, the energetics and behavior of hydrogen and hydrogen-helium gas bubbles will be investigated.